PEMBELAJARAN MENULIS DESKRIPSI DENGAN MEDIA GAMBAR - Puji Suprihatin (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2015)
The general purpose of the research was describe learning to write description with picture media of the fourth graders of the SDN Jetis IV Lamongan. Especially, the research had purpose to describe the planning, the implementation, the assessment of learning, and the effectiveness of the use of picture media in the learning. This research was designed using approach of descriptive-qualitative. The data of this research was schedule, implementation, and assessment of learning to write description with picture media. The source of the research was teacher and student of the fourth graders of SDN Jetis IV Lamongan in the academic year of 2013/2014. To collecting the data, the researcher use documentation technique, observation and test. The result of this research showed that the planning of learning to write description with picture media was marked by has good lesson plan although there were some matter what must was perfected. The implementation of learning was divided by three steps: pre writing step, drafting, as well as repair and documentation. The assessment of learning was marked by rubric of assessment either process assessment or result assessment so rubric of assessment that was prepared by the teacher had complete.